To 80 anniversary of Victor Danylenko - Б. В. Даниленко; Є. П. Шоферістов (Plant Varieties Studying and Protection)
The brief biographical information and the results of industrial and biological study of fruit crops varieties in steppe zone of the Crimea have been given. Widely spread varieties for industrial, collective and private orchards in Ukraine studied by V.V. Danylenko have been given. The main published workes of V.V. Danylenko have been given.